Case Report: Air–fluid point: a specific ultrasound sign for the diagnosis of hydropneumothorax in newborn infants - Liu, Jing; Jiang, Peng (Frontiers in Pediatrics, 2025)
Currently, lung ultrasound (LUS) is widely used worldwide for the diagnosing conditions such as neonatal pneumothorax (PTX) and pleural effusion, which are both common conditions during the neonatal period. However, the coexistence or simultaneous occurrence of both conditions, namely, hydropneumothorax, is relatively rare in clinical practice. Ultrasound enables a reliable diagnosis and can be used to guide and monitor appropriate treatment. In this case report, we describe a new ultrasound sign, the air–fluid point, which we propose as a specific sign for the diagnosis of neonatal hydropneumothorax.